Development of Local Wisdom-Based PBL using Paper Puppets to Improve Student’s Creativity - Sofiana, Eli; Nur Fadila, Kamila Nisa; Wulandari, Murfiah Dewi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research aims to develop a project-based learning method (Project Based Learning) that integrates local wisdom through the use of paper puppets, with a focus on improving the creative thinking of class III students in elementary schools. The development method used is the ADDIE model, which includes five main steps: Analysis, Design, Development, Implementation, and Evaluation. At the analysis stage, this research evaluates students' needs and characteristics and details the learning objectives to be achieved. The next step, namely design, involves designing a local wisdom-based project curriculum using paper puppets. The development process involves creating learning materials, resources, and other supporting tools that suit design needs. Implementation was carried out in class III, with data collection techniques in the form of observations and questionnaires to assess students' interest and understanding of the learning material. In addition, triangulation techniques were used to ensure the validity of the data collected. The evaluation results show that the average percentage of validity of aspects of students' attractiveness and understanding reaches an adequate level, with a total of 88.1% validity achieved. These findings provide a positive contribution to the development of a project-based learning model by utilizing local wisdom through paper puppets. The application of the ADDIE Method together with the use of data collection techniques provides a strong foundation in planning, developing, and evaluating the effectiveness of learning implementation.